Families, care and work in European Mediterranean Countries: findings and lessons from a comparative analysis of work-life balance policies - Pandolfini, Valeria (Italian Sociological Review, 2014)
The article explores work-life balance policies in five European Mediterranean countries: France, Greece, Italy, Spain and Turkey. The aim is to analyze how the interplay among different role of state, markets, third sector and families shapes work and family-care dimensions, within the economic, social, cultural contemporary context and the challenges prompted by the conditions of global crisis. Trough a cross-national comparison using Eurostat and Oecd data, it draws a synthesis of national labor markets’ features, shows the main trends regarding families’ size, composition and models and presents statutory Maternity, Paternity and Parental leave arrangements, early childcare services’ availability and family allowances system. Findings identify common aspects and differences among countries’ regulations, confirming the relationship between work-life balance policies and the different socio-economic contexts as well as cultural patterns and welfare regimes. The article conclude providing recommendations for politics to close the gap between today’s work and family realities and policies and practices governing their interrelationships, reflecting on the potential impact not only on individuals, but also on organizations and society.